Factors associated with abnormal findings on digital chest radiographs in asymptomatic workers in Lima, Peru - Murguía-Valdivia, Ludy (2021)
Introduction: Posteroanterior Chest X-Ray (CXR) is usually performed as a routine exam for workers’ health surveillance, but their benefits are discussed and controversial. Our investigation described the associated factors with abnormal digital CXR in workers without respiratory symptoms. Materials and methods: An analytical cross-sectional observational study was performed, including 24 069 digital CXR obtained from workers without respiratory symptoms who performed their workers’ health surveillance at an accredited occupational health center in Lima, Perú, from 2016 to 2019. Results: Of the 24069 asymptomatic workers, 1166 (4.84%, 95% CI [4.58-5.12]) had abnormal radiography. The main findings were found in the lung parenchyma and of these, sequential images of tuberculosis were the most frequent. It was observed that workers older than 50 years (RP(a) = 6.34), those with low weight (RP(a) = 2.71) and those with a history of pulmonary pathology (RP(a) = 6.19) were more likely to have abnormalities on pulmonary radiography. Conclusions: Due to the low frequency of abnormal digital Chest X-Ray (CXR), it is not useful as an early detection of respiratory pathology in the population studied, however it should be considered in those over 50 years with a history of respiratory disease and/or low weight. It is important to carry out more studies that confirm our results.